BEE informed: a diagnosis of black economic empowerment and its role in the political economy of South Africa - Lindsay, Donald Mitchell (My University, 2016)
The study investigates the South African phenomenon called black economic empowerment (BEE). Drawing on the historical record and theories in the fields of public policy, institution theory, and political economy, the roots of BEE are traced to the late apartheid era where it is shown to have emerged as an institutional response to events taking place in the transition to democracy. The study then tracks the development of the institution in the post-‐1994 era as it expanded through the medium of formal policymaking processes. Whereas BEE is widely presented as an initiative of the ANC government, the study draws on public policy theory to demonstrate how it has largely been driven by organisations outside of government. Further, that the character of the various BEE policies has reflected a situation of inadequate economic growth, combined with changes in the pattern of power relations in the post-‐apartheid era. While the study supports the need for interventions by the state to effect change in the economic order, it finds that BEE policies have been badly designed and implemented and have had little positive developmental impact. Moreover, with government coming under increasing pressure to deliver on its promise of ‘A Better Life for All’, amid wholly inadequate levels of economic growth, BEE policy is increasingly being used as a vehicle for the redistribution of rents rather than the creation thereof.
Thesis submitted in fulfilment of the requirements for the Degree Doctor of Philosophy in Sociology Department of Sociology University of the Witwatersrand June 2015